Gossypol is a natural product with good antimalarial activity against Plasmodium falciparum clinical isolates - Jersley D. Chirawurah; Felix Ansah; Samuel Blankson; Bridget Adikah; Silas Nkansah Yeboah; Lucas Amenga-Etego; Gordon A. Awandare; Yaw Aniweh (Scientific Reports)
Abstract Gossypol has demonstrated significant antimalarial activity against chloroquine-resistant and susceptible Plasmodium falciparum parasites. However, data on its potency in clinical isolates of P. falciparum remains limited. This study aimed to assess the potency of gossypol against six laboratory strains and twenty-one clinical isolates of P. falciparum using optimized growth inhibition assays. Additionally, parasites with reduced susceptibility to gossypol were selected using the P. falciparum Dd2 background (Dd2_3.5 µM) and tested for cross-resistance to chloroquine, dihydroartemisinin (DHA), and three Malaria box compounds (MMV006087, MMV085203, and MMV008956). On average, gossypol was found to be twice as potent against the laboratory strains compared to the clinical isolates, with IC₅₀ values of 6.490 µM and 11.670 µM, respectively. Notably, Dd2_3.5 µM parasites displayed increased sensitivity after three months of exposure but developed decreased susceptibility after six months. Importantly, these gossypol-tolerant parasites showed no cross-resistance to chloroquine, DHA, or the three Malaria box compounds. These findings suggest that gossypol is effective against P. falciparum and holds potential as part of combination therapy with existing antimalarials. Furthermore, these results may support the identification of new antimalarial agents that are effective against drug-resistant malaria parasites.